2004
DOI: 10.1385/abab:118:1-3:243
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore Production by a Marine <I>Pseudomonas aeruginosa</I> and Its Antagonistic Action Against Phytopathogenic Fungi

Abstract: A marine isolate of fluorescent Pseudomonas sp. having the ability to produce the pyoverdine type of siderophores under low iron stress (up to 10 microM iron in the succinate medium) was identified as Pseudomonas aeruginosa by using BIOLOG Breathprint and siderotyping. Pyoverdine production was optimum at 0.2% (w/v) succinate, pH 6.0, in an iron-deficient medium. Studies carried out in vitro revealed that purified siderophores and Pseudomonas culture have good antifungal activity against the plant deleterious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 16 publications
5
29
1
Order By: Relevance
“…A marine isolate of fluorescent Pseudomonas sp. which has the ability to produce the pyoverdine has been found to inhibit the growth of A. niger under in vitro conditions [20]. Similar results were [24] reported the specific production of fluorescein and pyocyanin by the Pseudomonas bacterium against Pythium.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…A marine isolate of fluorescent Pseudomonas sp. which has the ability to produce the pyoverdine has been found to inhibit the growth of A. niger under in vitro conditions [20]. Similar results were [24] reported the specific production of fluorescein and pyocyanin by the Pseudomonas bacterium against Pythium.…”
Section: Resultssupporting
confidence: 79%
“…Siderophore-mediated competition for iron by Pseudomonas sp. as well as induced resistance are primary mechanisms shown to be responsible for suppression of Fusarium wilt and this Pseudomonas culture and purified siderophore showed good antifungal activity against the plant deleterious fungi namely Aspergillus niger, A. flavus, A. oryzae, F. oxysporum and Sclerotium rolfsii [20]. Among the different Pseudomonas fluorescens tested, the intensity of HCN production was strong in P. fluorescens strains Pf1 and CPF1 followed by P. fluorescens strains CPF6 and CPF8.…”
Section: Resultsmentioning
confidence: 90%
“…The importance of siderophore production was reported by Lee et al (2001), Strains of Pseudomonas putida by producing siderophore induced systemic resistance in watermelon against gummy stem rot while the siderophore negative mutants failed to induce resistance. However, Manwar et al (2004) observed the ability of Pseudomonas aeruginosa to produce the pyoverdine type of siderophores that has good antifungal activity against plant deleterious fungi namely Aspergillus niger and A. flavus. Maximum concentration of ammonia production was observed in isolate MSA2 was 63 lg/ml (Fig.…”
Section: Phosphate Solubilizationmentioning
confidence: 99%
“…A fungal indicator organism (5 mm in diameter) was put in the middle of the same Petri dish. The inoculated Petri dish was cultured at 28°C for 48 h. The antagonistic action [12] was evaluated by measuring the diameter of the inhibition zones with penicillin as a positive control. For bacterial inhibition test, an indicator organism was spread on top of the Petri dish containing LB agar.…”
Section: Antagonistic Testmentioning
confidence: 99%